2020
DOI: 10.20463/pan.2020.0008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous lactate administration on fat metabolism and glycogen synthesis factors in rats

Abstract: Lactate has several beneficial roles as an energy resource and in metabolism. However, studies on the effects of oral administration of lactate on fat metabolism and glycogen synthesis are limited. Therefore, the purpose of the present study was to investigate how oral administration of lactate affects fat metabolism and glycogen synthesis factors at specific times (0, 30, 60, 120 min) after intake. [Methods] Male Sprague Dawley (SD) rats (n = 24) were divided into four groups as follows: the control group (0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Nevertheless, the effect of lactate intake on metabolism during exercise has not yet been directly investigated. In the aforementioned study by Kyun et al [ 24 ], it was also confirmed that glycogen synthesis- and fat metabolism-related factors increased over time after lactate administration. This study investigated the metabolic changes in exogenous lactate intake at rest over time; however, it did not determine the effect of lactate on metabolism during exercise.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Nevertheless, the effect of lactate intake on metabolism during exercise has not yet been directly investigated. In the aforementioned study by Kyun et al [ 24 ], it was also confirmed that glycogen synthesis- and fat metabolism-related factors increased over time after lactate administration. This study investigated the metabolic changes in exogenous lactate intake at rest over time; however, it did not determine the effect of lactate on metabolism during exercise.…”
Section: Introductionmentioning
confidence: 61%
“…Interestingly, we have previously confirmed the potential of lactate as a supplement by examining the effects of lactate intake at rest on metabolism [ 23 , 24 ]. The main aim of the present study was to investigate the effect of lactate intake on metabolism during exercise.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thirty-two rats were used in the study. They were randomly divided into 4 groups that were sacrificed at 0 min (control group), 30 min, 60 min, or 120 min after lactate administration with an oral sonde (Figure 1) at a concentration of 2 g/kg [22,23]. All rats were fasted for 2 h before lactate administration and were euthanized by vertebral dislocation at the predetermined time points.…”
Section: Animal Protocolmentioning
confidence: 99%
“…Immediately after sacrifice, 3 mL blood samples were obtained from the arteries, and skeletal muscle tissues (plantaris) were quickly removed, frozen in liquid nitrogen, and stored at −80 • C until analysis. oral sonde (Figure 1) at a concentration of 2 g/kg [22,23]. All rats were fasted for 2 h before lactate administration and were euthanized by vertebral dislocation at the predetermined time points.…”
Section: Animal Protocolmentioning
confidence: 99%